Research and application of high−temperature drilling fluid designed for the continental scientific drilling project of Songliao Basin, China. Issue 1 (31st March 2022) - Zheng, Wenlong; Wu, Xiaoming; Huang, Yuming
ABSTRACT: Well Songke−2 is the main hole of the Continental Scientific Drilling Project of Songliao Basin, China, and its bottom hole temperature is estimated to exceed 240°C in the fourth spud at the well depth of 5800 m. To ensure that the drilling fluid could meet the demand of high temperature resistance, different components, including clay, filtration reducers and anti−collapse additives, of the high–temperature drilling fluid system were optimized through thermal stability tests. Comprehensive test results suggested that the optimal bentonite content to be 4% (w/v). Compared with other materials of the same type, polymer filtration reducers SO−1 and HLW−1, as well as sulfonation additive LOCKSEAL were demonstrated to have stronger resistance to high temperature. The proposed high temperature drilling fluid formula exhibited good thermal stability, rheological behaviour, anti−contamination capacity and shale inhibition property. Finally, a great success of the formula was practically obtained in the field application during the following−up core drilling project.